Innovative method to produce large-area freestanding functional ceramic foils - Leighton, Glenn J. T.; Jones, Paul M.; Lonne, Quentin; Dorey, Robert A.; Giuliano, Fabien (Elsevier, 2018)
Using thick and thin films instead of bulk functional materials presents tremendous advantages in the field of flexible electronics and component miniaturization. Here, a low-cost method to grow and release large-area, microscale thickness, freestanding, functional, ceramic foils is reported. It uses evaporation of sodium chloride to silicon wafer substrates as sacrificial layers, upon which functional lead titanate zirconate ceramic films are grown at 710 °C maximum temperature to validate the method. The freestanding, functional foils are then released by dissolution of the sacrificial sodium chloride in water and have the potential to be integrated into low-thermal stability printed circuits and flexible substrates. The optimization of the sodium chloride layer surface quality and bonding strength with the underlying wafer is achieved thanks to pre-annealing treatment.
Keywords: Freestanding functional foils; NaCl sacrificial layers; PZT ceramic films; Ferroelectric